Applications and Engineering Analysis of Lotus Roots under External Water Pressure - Yiyun Zhu; Chang Jiang Wang; Diane Mynors (Applied Bionics and Biomechanics)
Engineers can learn from nature for inspirations to create new designs. The internal structure of lotus roots with several oval holes was studied in this paper for engineering inspirations. The structural performance of lotus roots under outside water pressure was simulated and compared with various cross-sectional areas. The distribution of stresses in the cross-sectional area of lotus roots was analysed and presented. It was found that the maximum compressive stresses in the cross-sectional area of lotus roots were occurring at the long axis ends of the holes. This was very different from that of circular holes. Further analysis on the triaxiality factors revealed that the cross-sectional area of the lotus root resulted in large areas of high triaxiality factors. The resulting hydrostatic stress in the cross-sectional area of lotus root ranges from zero to 2.7 times the applied outside pressure. In contrast, the hydrostatic stress in a cylindrical cross-sectional area is a fixed value. The study showed that the lotus root and the orientation of the oval holes could be mimicked in the design of new structures, for example, underwater pipes and vessels.